Lattice Constants Analysis of Tantalum Oxide Doped Lead Zirconium Titanate Ceramic by Delphi Program - Irzaman Irzaman; Y. Darvina; P. Arifin; M. Budiman; M. Barmawi (Indonesian Journal of Physics, 2005)
Ceramics of PbZrxTi1-xO3 (PZT) and 0.5 %, 1 %, 1.5 % tantalum oxide doped PbZr0.525Ti0.475O3 (PTZT) were successfully deposited by solid state reaction. The PZT and PTZT ceramics were analyzed by an x-ray diffraction (XRD). The XRD spectra were recorded by Diano type 2100E diffractometer using a CuKα (λcu = 1.54056 Å) radiation at 30 KV and 30 mA (900 watt). The spectra showed that PZT and PTZT ceramic are polycrystalline with tetragonal structure. The lattice constants analysis of the grown ceramics were described by Delphi program. Using Cohen’s and Cramer’s algorithms in the Delphi program, the lattice constants are a = b = 4.094 Å, c = 4.142 Å, c/a ratio = 1.012 for PZT ceramic, and a = b = 4.075 Å, c = 4.088 Å, c/a ratio = 1.003 for PTZT ceramic. The lattice constants are a = b = 4.094 Å, c = 4.142 Å, c/a ratio = 1.012 for PZT ceramic, a = b = 4.122 Å, c = 4.134 Å, c/a ratio = 1.003 for PTZT 0.5 % ceramic, a = b = 4.075 Å, c = 4.088 Å, c/a ratio = 1.003 for PTZT 1 % ceramic, a = b = 4.248 Å, c = 4.179 Å, c/a ratio = 0.984 for PTZT 1.5 % ceramic. Increasing tantalum oxide doping in PZT from 0 % to 1.5 % lead to the decrease in c/a ratio. The smaller value of the c/a ratio of PTZT ceramic than those of PZT ceramic is possibly associated with the anti site defects of Ta dopants.